Discovering SQL : a hands-on guide for beginners - Kriegel, Alex (Wrox beginning guides, 2011)
Teaching the SQL skills that businesses demand when hiring programmers If you're a SQL beginner, you don't just want to learn SQL basics, you also want to get some practical SQL skills you can use in the job market. This book gives you both. Covering the basics through intermediate topics with clear explanations, hands-on exercises, and helpful solutions, this book is the perfect introduction to SQL. Topics include both the current SQL:2008 standards, the upcoming SQL:2011 standards, and also how to use SQL against current releases of the most popular commercial SQL databases, such as Oracle